GE_GERICHTE C/4204/2012 vom 2. Dezember 2013 - GE Cour de justice (2013)
BAIL À LOYER; ACTION EN PAIEMENT; FORMALISME EXCESSIF; DROIT À LA PREUVE; COMPENSATION DE CRÉANCES | Cst.29; CC.8; CO.257c; CO.120